2011
DOI: 10.1016/j.istr.2011.09.008
|View full text |Cite
|
Sign up to set email alerts
|

The threats of social networking: Old wine in new bottles?

Abstract: Despite the many potential benefits to its users, social networking appears to provide a rich setting for criminal activities and other misdeeds. In this paper we consider whether the risks of social networking are unique and novel to this context. Having considered the nature and range of applications to which social networks may be applied, we conclude that there are no exploits or fundamental threats inherent to the social networking setting. Rather, the risks and associated threats treat this communicative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 5 publications
0
21
0
1
Order By: Relevance
“…Consequently, individuals are challenged to take opposing views into consideration with the result that it fosters political comprehension of diverse perspectives (Binder et al 2009). According to Weir, Toolan, and Smeed (2011), this eventually induces convergence of ideology through the modification of political views. Notably, empirical research has suggested that exposure to different viewpoints tends to enhance awareness, and tolerance, of the legitimate arguments regarding opposite political perspectives (Johnson et al 2013;Wicks, Wicks, and Morimoto 2014).…”
Section: Social Network Heterogeneity and Polarisationmentioning
confidence: 99%
“…Consequently, individuals are challenged to take opposing views into consideration with the result that it fosters political comprehension of diverse perspectives (Binder et al 2009). According to Weir, Toolan, and Smeed (2011), this eventually induces convergence of ideology through the modification of political views. Notably, empirical research has suggested that exposure to different viewpoints tends to enhance awareness, and tolerance, of the legitimate arguments regarding opposite political perspectives (Johnson et al 2013;Wicks, Wicks, and Morimoto 2014).…”
Section: Social Network Heterogeneity and Polarisationmentioning
confidence: 99%
“…Due to the extensive use of social media platforms in facilitating and supporting illegal activities, law enforcement agencies are now employing these websites as a source of intelligence that allows them to obtain information and arrest criminals [32]. To support law enforcement agencies in this task several research teams have developed designated automatic tools that allow surveilling criminals' social media accounts, collecting relevant data, and analyzing it [33][34].…”
Section: Social Media and Crimementioning
confidence: 99%
“…Prior research found that hackers and solicitors become increasingly reliant on SNSs to contact target victims 65. They distribute malware through SNSs and design phishing postings to seduce SNS users 66. For instance, if she or he posts a photo of a newly purchased auto vehicle, hackers are likely to design phishing information pertaining to auto insurance.…”
Section: Discussionmentioning
confidence: 99%
“… 65 They distribute malware through SNSs and design phishing postings to seduce SNS users. 66 For instance, if she or he posts a photo of a newly purchased auto vehicle, hackers are likely to design phishing information pertaining to auto insurance. Show-off posts on SNSs increase the risk of privacy invasion.…”
Section: Discussionmentioning
confidence: 99%